Fluvial transformations in the lower Reventazón-Parismina basin, Costa Rica - Piedra Aguilar, Fabio (2025)
An analysis using aerial photographs and satellite images was conducted on the courses of the Parismina and Reventazón rivers, near their confluence at Dos Bocas. Since 1973, the opening of a branch of the Parismina River, known as Quebrada Seca, has been observed, followed in later years by an increase in water infiltration through the Negritos and Sardinas channels. Currently, the waters of the Parismina River flow northward, creating a new course through its former branch at Quebrada Seca, which has separated its flow from the original confluence with Reventazón River. Its presents outlet into the Caribbean Sea occurs through the old Jalova Lagoon (southern boundary of Tortuguero National Park), approximately 7 km northwest of the town of Barra de Parismina. The Reventazón River, in turn, has shown alterations in its fluvial dynamics since 2016, occupying part of the abandoned course of the Parismina River. The modification of the river courses has occurred in three stages: (1) the Parismina River historically followed its course toward the Reventazón River, possibly until 2010, subsequently flowing into the Caribbean Sea at Barra de Parismina, (2) water infiltration and stagnation developed in the abandoned course of the Parismina River between 2010-2017, and (3) a reversal in flow direction occurred, leading to the Parismina River establishing its new course through Quebrada Seca starting in 2017. This work demonstrates the dynamic and changing nature of fluvial regimes.